2003
DOI: 10.1165/rcmb.2002-0095oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial Cells Release MIP-3α/CCL20 in Response to Cytokines and Ambient Particulate Matter

Abstract: The initiation and maintenance of airway immune responses in Th2 type allergic diseases such as asthma are dependent on the specific activation of local airway dendritic cells (DCs). The cytokine microenvironment, produced by local cells, influences the recruitment of specific subsets of immature DCs and their subsequent maturation. In the airway, DCs reside in close proximity to airway epithelial cells (AECs). We examined the ability of primary culture human bronchial epithelial cells (HBECs) to synthesize an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
182
3
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(201 citation statements)
references
References 41 publications
8
182
3
8
Order By: Relevance
“…CCL20 expression, but not that of inflammation-related chemokines, determines LC homing in the epidermis (23), the tonsils and probably also in the lung (24). CCL20 secretion by BEC was previously reported after exposure to allergen, but only in allergic asthmatic patients and to diesel exhaust particles (11,12). Therefore, CCL20 secretion is only induced by strong signals in BEC such as pathogen exposure or by proinflammatory mediators present within the lung environment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…CCL20 expression, but not that of inflammation-related chemokines, determines LC homing in the epidermis (23), the tonsils and probably also in the lung (24). CCL20 secretion by BEC was previously reported after exposure to allergen, but only in allergic asthmatic patients and to diesel exhaust particles (11,12). Therefore, CCL20 secretion is only induced by strong signals in BEC such as pathogen exposure or by proinflammatory mediators present within the lung environment.…”
Section: Discussionmentioning
confidence: 93%
“…Recent data suggest that DC behavior is locally controlled by lung environment and particularly by bronchial epithelial cells (BEC) (9 -11). In addition to GM-CSF, these BEC produce several cytokines and chemokines and express adhesion molecules potentially involved in DC traffic, as shown after exposure to diesel exhausted particles or allergens (6,11). In both allergic patients and nonatopic subjects, allergen-exposed BEC trigger the recruitment of monocyte-derived DC (MDDC) precursors through the secretion of CCL2, CCL5, and CXCL10.…”
mentioning
confidence: 99%
“…Further, several lines of evidence have proposed that bronchial epithelial cells are targeted by respirable pollutants in much the same way as the abundant DC that interdigitate those epithelial cells and 'survey' the external environment [51][52][53] . It has been shown that ambient PM also induces epithelial cells to produce amphiregulin, granulocyte-macrophage colony-stimulating factor and MIP-3 ␣ [53][54][55][56] , that are known to induce recruitment and survival of DC.…”
Section: Discussionmentioning
confidence: 99%
“…These data are corroborated by experiments on animals lacking the TRIF adaptor molecule used by TLR4. Hence, the flagellin-mediated lung innate response depends solely on the TLR5 receptor and the MyD88 adaptor.Airway epithelial cells also produce chemokines (such as CCL20) that attract monocytes/dendritic cells and that may potentiate adaptive immunity in a mucosal adjuvant mechanism [34,[51][52][53][54][55]. In contrast, flagellin may directly activate lung dendritic cells [48,56].…”
mentioning
confidence: 99%